2014
DOI: 10.1007/s11010-014-2301-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-esterified fatty acids promote expression and secretion of angiopoietin-like protein 4 in calf hepatocytes cultured in vitro

Abstract: An elevated plasma non-esterified fatty acids (NEFA) concentration is an important indicator of negative energy balance, which is often associated with metabolic diseases such as fatty liver and ketosis. Angiopoietin-like protein 4 (ANGPTL4) is a hepatokine that plays important roles in the regulation of lipid metabolism. However, the direct effects of high concentrations of NEFA on ANGPTL4 expression and secretion in hepatocytes from cows are not entirely clear. The objective of this study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…ANGPTL4 is mainly expressed in liver and adipose tissues [38] and plays important roles in the regulation of lipid metabolism. Previous studies have suggested that a SNP in ANGPTL4 is associated with intramuscular fat [39] and the expression level of ANGPTL4 affects meat quality traits of pigs [40]. Recent studies have shown that acyl-CoA synthetase family member 3 (ACSF3), in which DMRs in promoter region were found in the present study to be negatively correlated with the gene expression level, plays a critical role in mammal fatty acid synthesis in mitochondrion [41].…”
Section: Discussionmentioning
confidence: 53%
“…ANGPTL4 is mainly expressed in liver and adipose tissues [38] and plays important roles in the regulation of lipid metabolism. Previous studies have suggested that a SNP in ANGPTL4 is associated with intramuscular fat [39] and the expression level of ANGPTL4 affects meat quality traits of pigs [40]. Recent studies have shown that acyl-CoA synthetase family member 3 (ACSF3), in which DMRs in promoter region were found in the present study to be negatively correlated with the gene expression level, plays a critical role in mammal fatty acid synthesis in mitochondrion [41].…”
Section: Discussionmentioning
confidence: 53%
“…The expression of Angptl4 is also regulated through a synergistic induction of the lipid-sensing peroxisome proliferator-activated receptors (PPARs) α, β, and γ (40). Among the lipids, fatty acids (FA) are the best-recognized inducers of Angptl4 expression (16, 41-43). Although FA are an energy source, they are also recognized as regulators of inflammation, and it has been suggested that PPARs play an important role in FA-dependent gene regulation (44).…”
Section: Discussionmentioning
confidence: 99%
“…All experimental procedures were approved by the Institutional Animal Care and Use Committee of Northwest A&F University, Yangling, People's Republic of China. Hepatocytes were isolated using the collagenase perfusion method as previously described (Wang et al., ; Zhang et al., ). For each isolation procedure, the liver (caudate process) was obtained under sterile conditions from a neonatal Holstein calf (male) anesthetized with thiamylal sodium.…”
Section: Methodsmentioning
confidence: 99%